The relevant library : essays on adapting to changing needs - Gubnitskaia, Vera, 1960-; Smallwood, Carol, 1939-; Walter, Scott, 1967- (McFarland & Company, Inc., Publishers, 2018)
"In this collection of new essays, contributors share their experiences and ideas for keeping libraries integral to changing communities. Innovative approaches and best practices are discussed for strategic planning, packaging, branding and marketing, funding issues, physical spaces, collection needs and trends, partnerships, programming and services, professional education, and staffing"--